Design and Synthesis of Chitosan—Gelatin Hybrid Hydrogels for 3D Printable in vitro Models - Magli, Sofia; Rossi, Giulia Beatrice; Risi, Giulia; Bertini, Sabrina; Cosentino, Cesare; Crippa, Luca; Ballarini, Elisa; Cavaletti, Guido; Piazza, Laura; Masseroni, Elisa; Nicotra, Francesco; Russo, Laura (Frontiers in Chemistry, 2020)
The development of 3D printable hydrogels based on the crosslinking between chitosan and gelatin is proposed. Chitosan and gelatin were both functionalized with methyl furan groups. Chemical modification was performed by reductive amination with methyl furfural involving the lysine residues of gelatin and the amino groups of chitosan to generate hydrogels with tailored properties. The methyl furan residues present in both polymers were exploited for efficient crosslinking via Diels-Alder ligation with PEG-Star-maleimide under cell-compatible conditions. The obtained chitosan-gelatin hybrid was employed to formulate hydrogels and 3D printable biopolymers and its processability and biocompatibility were preliminarily investigated.